(3Pjd Ydi (B((3Pjd Ydi JajjOGJ GdaTJGdj(B)s - (3CHh YHO Gddg eMeO Hf CMeO Hf eMeO Hf CMeO GdecdGJjs; (3eMeO Hf CMeO Hf YHO Gdedc, CHh YHO Gddg GdaTJGdj(B: (3bGVj aGS,J (B777 (3g` s
(3ChdgG (B:s
(3hReQ GHf GHQGgje Tdh hRgOg Mdi LjOg ai GdYde ZjQ eYWd s
(3BNQgG (B:s
(3ahGYLHG ddOgQ ZjH UQag TehS Ydhe ai GdJQGH djHJdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B231s
(3hjHOh CfgG fGbUI dCfg jhLO aj Pjd GdUaMIhEf PgGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B225 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B286s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B187 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(487 (3O(B) s
Keywords: (3GdJGQjNs